PENGARUH PENGGUNAAN MOBIL BANKING TERHADAP MINAT MASYARAKAT MENGGUNAKAN LAYANAN PERBANKAN DIGITAL MODERN - Qoribul Lathif; Siti Nikmatus Salamah; Amanatus Solehah (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of digital technology has encouraged the transformation of banking services into more modern and practical systems. Mobile banking has become one of the most widely used digital banking innovations because it offers easy access, time efficiency, and security in conducting financial transactions. This study aims to analyze the influence of mobile banking usage on public interest in using modern digital banking services. The research method used is a quantitative method with a survey approach through the distribution of questionnaires to users of digital banking services. The data analysis technique was conducted using simple linear regression analysis to determine the relationship between the variables of mobile banking usage and public interest. The results of the study indicate that the use of mobile banking has a positive and significant effect on public interest in using modern digital banking services. The higher the level of convenience, security, and perceived benefits in using mobile banking, the higher the public interest in utilizing digital banking services. This study is expected to serve as a reference for banking institutions in improving the quality of digital services to attract and maintain customer interest in the era of digital transformation.